BiSbTe alloy with high thermoelectric and mechanical performance for power generation. (September 2022) - Guo, Fengkai; Sun, Yuxin; Qin, Haixu; Zhu, Yuke; Ge, Zhenhua; Liu, Zihang; Cai, Wei; Sui, Jiehe
Abstract: The zone-melted Bi2 Te3 based alloys with excellent near room temperature figure-of-merit have dominated the field of commercial thermoelectric materials for many years. However, the poor mechanical strength restricts their application on the hot emerging miniature TE devices. Herein, we adjust the Bi/Sb ratio of the nanotwins strengthened Te-deficient Bi0.4 Sb1.6 Te2.98 alloy, obtaining a mechanically robust p-type Bi2 Te3 based alloy with a high peak zT of 1.33 at 150 °C and an eminent zT ave of 1.16 over 30 to 250 °C. Then, taking this alloy and Cu0.01 Bi2 Te2.7 Se0.3 as the p-type and n-type legs respectively, a module possessing high conversion efficiency of ∼4.8% at a temperature difference of 270 °C is fabricated, which paves an effective way to develop robust miniature (Bi, Sb)2 Te3 -based TE devices. Graphical abstract: Image, graphical abstract